Incidence of Medication Errors in a Tertiary Care Hospital in South-India - Ramesh, Ganpisetti; Sundeep, Kanneganti; Anitha, Challa; Malika, Sravya; Samyuktha, K Rani; Sharmila, SK; Babu, P Srinivasa (Indian Journal of Pharmacy Practice)
Aim and Objectives: 1) To assess incidence of medication errors. 2) To evaluate percentage of patients admitted with adverse drug reaction. 3) To evaluate percentage of Error Prone Abbreviations. 4) To analyze the adverse drug event in Patients Receiving High Risk Medication. Methods and Search Strategy: A systematic review of literature related to Medication errors in prescribing, transcribing, dispensing, administration and documentation in various subjects, error prone abbreviations, adverse drug events in patients receiving high risk medication were collected. The following electronic databases were searched: Embase, Pubmed, EBSCO, Allied Health Literature. Results: We reviewed 20796 medication orders and found 1710 medication errors (8.5%), 214 Error Prone Abbreviation (1.1%), 5 patients admitted with Adverse drug reaction (0.45%), 3 adverse drug events in Patients Receiving High Risk Medication (0.27%). Among the 1710 medication errors (8.5%) – 619 transcribing errors (3.29%), 397 prescribing errors (2.11%), 13 dispensing errors (0.06%), 357 documentation errors (1.89%), 214 EPA (1.14%), 5 near miss errors (0.02%), 55 missed dose errors (0.29%) were found. Conclusion: Now a days medication errors are being observed most commonly in a tertiary care hospital. Of the observed medication errors transcribing errors were observed more commonly followed by to prescribing, documentation, EPA, dispensing, missed dose errors and near miss errors. We can overcome these medication errors by educating physicians, nurses regarding the areas where medication errors are more prone to occur.
Keywords: Medication error; Prescribing error; Dispensing error; Administration error; Documentation error; Transcribing error; EPA (Electronic prior authorization); Near miss; Missed dose.